A Community Without a Drug Problem? Black Drug Use in Britain - Kalunta-Crumpton, Anita (Social justice, 2004)
Part of a special issue on resisting militarism and globalized punishment. A study was conducted to explore the nature of the drug problems experienced by the black clients of a London drugs project in London, England. Emphasis is placed on the health and social problems experienced by participants.